Welcoming the newcomers our way - Takaindisa, Joyce (2025)
Mainstream perceptions in public, media, and policy discourses predominantly assign the responsibility of integrating internally displaced persons (IDPs) to local and national institutions. Much academic attention has tended to focus on the role of state institutions in international migration, side-lining community-centric approaches of integration in internal migration or displacement. Moreover, the integration literature is predominantly Eurocentric, with a strong focus on integration dynamics in Europe and the USA as a ‘crisis.’ Consequently, the bulk of research studies have tended to focus on integration of persons who have crossed borders to seek refuge or asylum in another country, akin to what has been described as the mono-directional conceptual flow sourced in the Global North. Rarely do scholars and policy makers consider the role of traditional integration mechanisms in fostering social cohesion and peace among IDPs and receiving communities.